2019
DOI: 10.1002/evan.21810
|View full text |Cite
|
Sign up to set email alerts
|

Playing with language, creating complexity: Has play contributed to the evolution of complex language?

Abstract: We argue that enhanced play may have contributed to the emergence of complex language systems in modern humans (Homo sapiens). To support this idea, we first discuss evidence for an expansion of playing behavior connected to the extended childhood of modern human children, and the potential of this period for the transmission of complex cultural traits, including language. We then link two of the most important functions of play—exploration and innovation—to the potential for cumulative cultural evolution in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 107 publications
(213 reference statements)
0
12
0
Order By: Relevance
“…The emergence of complex language, giving modern humans a crucial fitness advantage, is a common explanation for the demise of the Neanderthal (Villa and Roebroeks 2014 ). It has been suggested that Neanderthals had a more restricted language system because of, for example, a shorter childhood (Langley et al 2020 ) or a restricted working memory (Rossano 2010 ).…”
Section: Darwinian Winners and Losersmentioning
confidence: 99%
“…The emergence of complex language, giving modern humans a crucial fitness advantage, is a common explanation for the demise of the Neanderthal (Villa and Roebroeks 2014 ). It has been suggested that Neanderthals had a more restricted language system because of, for example, a shorter childhood (Langley et al 2020 ) or a restricted working memory (Rossano 2010 ).…”
Section: Darwinian Winners and Losersmentioning
confidence: 99%
“…shows social and cognitive preparedness to engage in ritual (23,28,30,74). In overimitation, the sequence of modelled actions includes those that are causally actions tend to arouse over-imitation responses, which themselves may also be more memorable (9), and which may suppress innovation and change.…”
Section: Ritual and Ritual Actionsmentioning
confidence: 99%
“…Over-imitation is increasingly considered the most compelling way in which the mind (whether that of a modern H. sapiens child or now-extinct hominins) shows social and cognitive preparedness to engage in ritual [23,28,30,75]. In over-imitation, the sequence of modelled actions includes those that are causally irrelevant (e.g.…”
Section: Ritualization Of Culture Transmission?mentioning
confidence: 99%
See 1 more Smart Citation
“…Hominin life histories, as tracked through anatomical proxies, differed as did the provisioning of youngsters with, for instance, playthings . In this light, it has recently been suggested by the authors that children may, in fact, be one of the primary drivers of technological and cultural innovation—ultimately pushing humankind toward increasingly complex languages and technologies. In addition—and not trivially—this focus on children and their ontogenetic niches may also bring paleoanthropologists closer to understanding why innovations are unevenly distributed in space and time both before and after the emergence of fully modern humans.…”
Section: Introductionmentioning
confidence: 99%